The witch hunter - Seeck, Max, 1985- (Berkley, 2020)
"A shocking murder in an affluent Helsinki suburb has ties to the occult in this thrilling US debut from Finnish author Max Seeck. A bestselling author's wife has been found dead in a gorgeous black evening gown, sitting at the head of a formally set dinner table. Her most chilling feature - her face is frozen in a ghastly smile. At first it seems as though a deranged psychopath is reenacting the gruesome murders from the victim's husband's bestseller, The Witch Hunter. But investigator Jessica Niemi soon realizes she's not looking for a single killer but rather dozens of believers in a sinister form of witchcraft. They know her every move and are always one step ahead. As the bodies start piling up, Jessica knows they won't stop until they get what they want. And when her dark past comes to light, Jessica finds herself battling her own demons while desperately trying to catch a coven of killers before they claim their next victim"--